Effect of the phosphate and mineralogical composition on the movement and mineralization of glyphosate in clay soils - Dotor Robayo, Mónica Yadira; Martínez Cordón, Maria Jose; Okada, Elena (Springer, 2024)
Glyphosate is one of the most used herbicides worldwide. In rice paddy fields, it is usually applied for weed control during the pre-planting stage. Phosphate fertilizers may enhance herbicide displacement in the soil matrix. The objective of this study was to assess the effect of monoamoniun phosphate and the mineralogical composition on the movement and mineralization of glyphosate in clay soils (CS1; CS2 and CS3) in Colombia. Glyphosate miscible displacement experiments were performed in disturbed soil columns, with and without the addition of phosphate after the application of a pulse of N-(phosphonomethyl-14C) glycine. Simultaneously, 14C-glyphosate mineralization was measured indirectly by quantifying the amount 14C–CO2 released daily. At the end of the experiment, the columns were divided into six horizontal sections and glyphosate-bound residues were determined in the soil. The addition of phosphate decreased glyphosate retention time (in CS1 and CS2) and increased the total leached amount only in CS1 soil. Overall, more than 95% of the applied glyphosate was retained in the soil columns. Glyphosate mineralization half-life adjusted to a bi-exponential model, implying that one fraction degrades rapidly due to being more bioavailable, and the other fraction presents a slow rate of degradation and, that although high contents of kaolinite clays are important in the adsorption and translocation of the herbicide, the presence of calcites and divalent cations modify this process, favoring the persistence of the molecule in the soil. Glyphosate partitions into an easily degradable fraction and a more recalcitrant fraction adsorbed to kaolinite clays, calcites, and divalent cations. This fraction is less available for biodegradation thus favoring glyphosate persistence in soil.